A clinician's guide to biosimilars in oncology. (May 2016) - Rugo, Hope S.; Linton, Kim M.; Cervi, Paul; Rosenberg, Julie A.; Jacobs, Ira
Highlights: A biosimilar is a biological agent that is highly similar to a licensed biologic. Biosimilars may increase access worldwide to potentially life-saving biologics. Biosimilarity is established through analytical, nonclinical and clinical studies. Regulatory approval is based on the totality of evidence from the development program. Oncologists will have to decide whether and when to switch to biosimilars. Abstract: Biological agents or "biologics" are widely used in oncology practice for cancer treatment and for the supportive management of treatment-related side effects. Unlike small-molecule generic drugs, exact copies of biologics are impossible to produce because these are large and highly complex molecules produced in living cells. The term "biosimilar" refers to a biological product that is highly similar to a licensed biological product (reference or originator product) with no clinically meaningful differences in terms of safety, purity, or potency. Biosimilars have the potential to provide savings to healthcare systems and to make important biological therapies widely accessible to a global population. As biosimilars for rituximab, trastuzumab, and bevacizumab are expected to reach the market in the near future, clinicians will soon be faced with decisions to consider biosimilars as alternatives to existing reference products. The aim of this article is to inform oncology practitioners about the biosimilar development and evaluation process, and to offer guidance on how to evaluate biosimilar data in order to make informed decisions when integrating these drugs into oncology practice. We will also review several biosimilars that are currently in development for cancer treatment.